Pengaruh Gaya Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VII SMP N 1 Ampek Angkek Tahun Pelajaran 2022/2023 - Nelly Aprillia; Isnaniah Isnaniah; Emita Gusti (KOLONI, 2022)
Learning style is an important element that is considered in the learning process in order to realize the expected goals of learning mathematics. Learning style refers to the method of learning that students prefer, but there are still many students who do not know and understand their own learning style. The purpose of this study was to determine the effect of learning styles on students' mathematics learning outcomes in class VII SMP N 1 Ampek Angkek in the 2022 academic year. 2023. This type of research is correlational with the nature of Ex post facto research. The data collection technique used in this study was a questionnaire. Data analysis using SPSS. In accordance with the data analysis, it can be concluded: "(1) for learning styles on mathematics learning outcomes, the regression equation Y = 17.060 + 0.803 X is obtained. The tcount value > ttable with a significant level of 5%, namely 3.521 > 2.048, and the correlation coefficient value is 0.554 and R square or the coefficient of determination is 0.307 so that it can be interpreted that learning styles have a very small influence contribution, namely 30.7%, others are influenced by other factors outside the X variable. So it can be concluded that learning styles have a significant influence on learning outcomes mathematics for class VII students of SMP N 1 Ampek Angkek for the Academic Year 2022/2023”. Keywords: learning styles, learning outcomes of mathematics